Phylogenetic analysis of stemmed points from Patagonia: Shape change and morphospace evolution - Cardillo, Marcelo; Charlin, Judith (Journal of Lithic Studies, 2018)
This work is focused in the study of Patagonian lithic projectile points shape variation from a phylogenetic perspective pursuing three main aims: first, generate a model of projectile point shape diversification and morphospace evolution; second, estimate shape variation through time, and finally, assess the robustness of previous results using the same methods but in a larger sample with better spatial coverage. A previous work using geometric morphometric and cladistic methods suggested a pattern of general morphological diversification across Patagonia related, at least in part, to the spatial distance between cases, distinguishing two main clades in northern (43-45° S) and southern (50-52° S) Patagonia. In the present work to study this pattern in a more detailed level, a sample of ca. 1200 projectile points was used to obtain statistically different morphological classes performing unsupervised K-means searching. Shape characters were used to describe the different taxonomic units and to perform the phylogenetic analysis (through the Neighbor Joining and Maximun Parsimony methods) using as an ancestor the earliest point type known to the region (Fishtail point). The new results suggest that projectile points with longer and narrow blades and smaller stems evolved later in Patagonia and occupy a different sector of morphospace that could be related to the emergence of different technical systems, like the bow and arrow. However, these results do not support the previous ones of a projectile point diversification pattern mediated by spatial distance, maybe due to the reduction of contrast between the extreme north and south of Patagonia by the larger spatial coverage used in the present analysis.